Optimization of Gold Dissolution Parameters in Acidified Thiourea Leaching Solution with Hydrogen Peroxide as an Oxidant: Implications of Roasting Pretreatment Technology - Jeanne Pauline Munganyinka; Jean Baptiste Habinshuti; Gbetoglo Charles Komadja; Placide Uwamungu; Himanshu Tanvar; Grace Ofori-Sarpong; Brajendra Mishra; Azikiwe P. Onwualu; Scott Shuey (Metals, 2022)
The nature of gold (Au) ore deposits plays an essential role in determining the best gold recovery method as an alternative to cyanidation, considering environmental concerns. Thiourea (Tu) leaching of gold is an alternative lixiviant for treating sulfide gold ores and concentrates. The present study investigated the leaching behavior of Au from sulfide gold ore concentrates obtained from the Cripple Creek site (Newmont operated mine) using acidified thiourea solution. The concentrates containing pyrite, K-feldspar, quartz, and gypsum as major minerals were roasted before leaching to break down complex sulfides and improve the gold’s leachability. Parameters investigated include the leaching time (1–7 h), temperature (20–60 °C), pulp density (20–60 g/L), and thiourea concentration (20–60 g/L) to determine optimum conditions for Au dissolution. Hydrogen peroxide (H2O2) was used as an oxidizing agent and sulfuric acid (H2SO4) to maintain an acidic environment during the leaching process. The highest Au dissolution percentage of 96.2 was obtained after 6 h of leaching with 40 g/L thiourea at 60 °C, pH 1, and pulp density of 20 g/L. Based on the results presented in this work, the dissolution of gold with thiourea in an acidic solution would be a potential alternative to the traditional cyanide process, with the increase in understanding of the green leaching of Au from sulfide gold ores.